Explicating Ethical Corporate Marketing. Insights from the BP Deepwater Horizon Catastrophe: The Ethical Brand that Exploded and then Imploded - Balmer, John M. T.; Powell, Shaun M.; Greyser, Stephen A. 1935- (2011)
Ethical corporate marketing—as an organisational-wide philosophy—transcends the domains of corporate social responsibility, business ethics, stakeholder theory and corporate marketing. This being said, ethical corporate marketing represents a logical development vis-a-vis the nascent domain of corporate marketing has an explicit ethical/CSR dimension and extends stakeholder theory by taking account of an institution’s past, present and (prospective) future stakeholders. In our article, we discuss, scrutinise and elaborate the notion of ethical corporate marketing. We argue that an ethical corporate marketing positioning is a prerequisite for corporations which claim to have an authentic ethical corporate identity. Our article expands and integrates extant scholarship vis-a-vis ethical corporate identities, the sustainable entrepreneur and corporate marketing. In delineating the breadth, significance, and challenges of ethical corporate marketing we make reference to the BP Deepwater Horizon (Gulf of Mexico) catastrophe of 2010.
Keywords: Ethical corporate brands; Sustainability; Sustainable entrepreneurship; Ethical corporate identity; Corporate marketing; Ethical corporate marketing; Deepwater horizon; Brand positioning; BP brand